EXPRESS-METHOD OF THE STUDY OF THE SEDIMENT OF PROSOCIAL BEHAVIOR OF ADOLESCENTS - Olha Yezhova; Valentyna Kyrychenko; Valeria Necherda (National Academy of Educational Sciences of Ukraine, 2019)
The problem of diagnosing of the formation of prosocial behavior of adolescents - students of the institution of secondary education is considered. The rapid method "Prosocial behavior by pupils' eyes" of research on the formation of adolescents of prosocial behavior, developed by the scholars of the Institute of Problems on Education of the National Academy of Educational Sciences of Ukraine, is presented. Prosocial behavior in the article is defined as a system of actions and deeds of an individual, due to the conscious adoption of socially significant norms and values, the ability to constructively solve interpersonal and group conflicts, the unresponsiveness to risky ways of polysubject interactions, and the ability to self-fulfillment in various types of socially significant activities. This definition applies to pupils of all ages of different social groups. On the basis of the analysis of psychological and pedagogical literature and educational practice, criteria, indicators and levels of formation of prosocial behavior of adolescents of vulnerable categories were determined and an express method of research of the formation of prosocial behavior of adolescents-pupils of a secondary school was elaborated, which would facilitate the optimization of educational influences. The proposed rapid method of research on the formation of prosocial behavior is considered as a preliminary diagnostic tool, useful for planning and correction of educational work in a secondary education institution.